Comparative analysis of discourse between Hugo Chávez and Pablo Iglesias. How does the new political language influences citizenship? - Linares Rodríguez, Virginia; Garcés Claros, Diego (Estudios sobre el Mensaje Periodístico, 2018)
The following analysis pretends to establish a discursive comparison between Hugo Chávez Frías (Former President of Venezuela) and Pablo Iglesias (general secretary of Podemos in Spain), and how the new political language promoted by both leaders had affected directly in the citizens. Likewise, to seek and emphasize the origin of the transmitted messages and, in every case, study why they accomplished to have a protagonist in people’s life, from a political, social and communicative point of view.
Keywords: Political speech; new language; citizenship.